Performance of black pepper in coconut based high density multi-species cropping system under different nutrient managements - H.P. Maheswarappa, P. Subramanian; R. Surekha, T.J. Zachariah; Ravi Bhat, V. Selvamani (Journal of Plantation Crops, 2016)
Coconut based high density multi-species cropping system (HDMSCS) is recommended to obtain maximum income and better utilization of resources. The crops grown under HDMSCS include fruits, vegetables, spices etc. Black pepper (Piper nigrum L.), an important spice crop, is generally a componentÂ under coconut based cropping systems. In the present study, the performance of black pepper under coconut based HDMSCS involving banana, nutmeg, cinnamon, and other annuals viz., turmeric, ginger and elephant foot yam as intercrops, was evaluated, in terms of yield and quality of black pepper. The observations, recorded for four years (2009-10 to 2012-13) under three different nutrient management practices, indicated no significant difference in yield and quality parameters of black pepper. The pooled data of four years indicated a mean pepper yield of 2.4 kg vine-1, and quality parameters viz., per cent of oil, oleoresin, piperine and bulk density (g L-1) were 2.3, 9.8, 3.1 and 500.7, respectively. Under different nutrient management practices, the yield of both black pepper and coconut increased by 166 and 9 per cent, respectively, compared to the pre-treatment period (2005-07). The present study indicated that there was no reduction in yield of coconut when black pepper was grown in the basin and depending upon the availability of resources, farmers can follow the nutrient management practices.